The Effect of Aqueous Solution of Hibiscus sabdariffa (Zobo Drink) on Albino Wistar Rats Ovarian Tissue - Akafa, Tensaba Andes; Ujah, Williams Oche; Eli, Isaac Kogi; Ayara, Charles; Makanjuola, Victor; Williams, Queen Uyo; Istifanus, Dafup Katdel; Akafa, Vika Tensaba; David, Izam Emmanuel; Iseko, Kingsley Iyoko; Akafa, Ranyang R. (African Journal of Medicine, Surgery and Public Health Research, 2024)
Hibiscus sabdarrifa is a flowering plant that grows in tropical regions. It is used in the preparation of a non-alcoholic beverage called Zobo drink. This current study investigated the ovarian histological changes and hormonal level outcome that occur after administration of Hibiscus sabdarrifa aqueous solution (Zobo drink) on albino Wistar rat. Twenty (20) female Wistar rats were purchased and divided into five (5) groups, group A, group B, group C, group D and group E with each group having four (4) Wistar rats. Group A, the control group was unexposed to any form of foreign substance. Group B were given 0.5ml of Zobo drink once daily (morning). Group C were given 0.5ml of Zobo drink twice daily (morning and afternoon). Group D were given 0.5ml of Zobo drink three times daily (morning, afternoon and evening). Group E were given the Zobo drink concurrently all through the day and water only at night. In the end, the rats were sacrificed and the ovaries were removed and fixed in 10% formalin saline solution. The ovaries were stained with hematoxylin and eosin. Their blood was collected through the femoral artery for hormonal level assay. The histological result of group A, B, C and D showed normal histological structures. Group E showed hemorrhage in the corpus luteum of the ovaries. The result of the hormonal analysis showed an increase in the level of progesterone, follicle stimulating hormone and luteinizing hormone and decrease in the level of estrogen all through the five groups. This lower estrogen level could impede menstruation. Therefore, Zobo drink can damage the ovary if taken in excess quantity and cause fluctuation in hormonal level of the ovary.